ANALISIS VALUE ENGINEERING PADA PROYEK PERUMAHAN PESONA GRIYA ASRI DI KABUPATEN KUDUS - Noviyanti, Emmi (Teknik Sipil, Fakultas Teknik Universitas Negeri Jakarta, 2022)
The need for housing continues to increase along with the increase in population. Housing development as an effort to meet the community's needs for housing. However, the limited land and competition from housing developers who offer housing in a higher segment and at a lower price, it can be concluded that there is a waste of costs in this housing development. Therefore we need a way to overcome this problem, namely by applying Value Engineering. This study aims to analyze the optimization of the calculation of the budget plan without reducing the quality and function of the building using the Value Engineering method. The analysis technique in Value Engineering in this study uses the comparative method with cost analysis. This method compares the advantages of the landcape design before the redesign and after the redesign by changing the house plan, appearance and number of house compositions on the site plan so that maximum benefits are obtained. Based on the results of the Value Engineering analysis on the Pesona Griya Asri housing project in Kudus Regency, the most profitable alternative design using Design C. The large increase in profits generated after Value Engineering was originally Rp. 407,938,977 to Rp. 847,970,184.